2014
DOI: 10.5847/wjem.j.issn.1920-8642.2014.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of non-biological artificial liver treatments for patients with acute liver failure complicated by multiple organ dysfunction syndrome

Abstract: BACKGROUND: Acute liver failure (ALF) caused by viral and non-viral hepatitis is often accompanied with severe metabolic disorders, the accumulation of toxic substances and continuous release and accumulation of a large number of endogenous toxins and inflammatory mediators. The present study aimed to investigate the effects of various combined non-biological artifi cial liver treatments for patients with acute liver failure (ALF) complicated by multiple organ dysfunction syndrome (MODS). METHODS:Thirty-one pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In addition, the ALSS with a single mode of action may not be sufficient to meet the treatment needs for the patients, so combination of different types of ALSS, using their respective advantages to complement each other, has become a favorable choice . Li et al applied a combination of PE, hemoperfusion (HP) and continuous veno‐venous hemodialysis filtration (CV‐VHDF) in patients with ALF, and the results showed that PE + HP + CVVHDF could effectively remove bilirubin . A study illustrated that PE combined with bilirubin adsorption can effectively remove toxins to improve liver function .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the ALSS with a single mode of action may not be sufficient to meet the treatment needs for the patients, so combination of different types of ALSS, using their respective advantages to complement each other, has become a favorable choice . Li et al applied a combination of PE, hemoperfusion (HP) and continuous veno‐venous hemodialysis filtration (CV‐VHDF) in patients with ALF, and the results showed that PE + HP + CVVHDF could effectively remove bilirubin . A study illustrated that PE combined with bilirubin adsorption can effectively remove toxins to improve liver function .…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Li et al applied a combination of PE, hemoperfusion (HP) and continuous veno-venous hemodialysis filtration (CV-VHDF) in patients with ALF, and the results showed that PE + HP + CVVHDF could effectively remove bilirubin. 25 A study illustrated that PE combined with bilirubin adsorption can effectively remove toxins to improve liver function. 26 Similarly, the results of the present study showed that DPMAS+PE had a significantly higher ability to reduce bilirubin than PE alone.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that PE and DPMAS could resulted in significant reduction in ALT, AST, TBIL, DBIL, TBA, and albumin levels in ACLF patients. 8,9,18,19 Li et al 5 reported that PE combined with HP could decrease TBIL and ALT levels more significantly than HP or PE alone. Therefore, different combinations of non-bioartificial therapies were more effective in improving severe metabolic disorders and removing accumulated toxic substances and inflammatory mediators caused by serious damage of liver cells.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma exchange (PE) using fresh frozen plasma (FFP) as replacement fluid is conventionally performed as the main treatment of liver failure for many years. PE can successfully remove both protein-bound and large molecules such as inflammatory mediators 5,6 ; but it is mainly restricted by increased risk of allergies and infections due to exposure to exogenous plasma. 7 Double plasma molecular adsorption system (DPMAS) is a modified hemoperfusion model that combines anion exchange resin and neutral macroporous resin.…”
Section: Introductionmentioning
confidence: 99%
“…Supportive extracorporeal therapy is a treatment that provides temporary and partial replacement of liver function, while also removing harmful substances and supplying beneficial biological substances to promote the regeneration and functional recovery of the patient’s liver cells [ 10 ]. However, since the effectiveness of supportive extracorporeal therapy alone is limited, there is growing interest in exploring different combinations of non-biological artificial liver methods [ 11 , 12 ]. Continuous venovenous hemodiafiltration and plasma exchange are used in conjunction as a bridging treatment in recovery without liver transplant and to extend care until liver transplant.…”
Section: Introductionmentioning
confidence: 99%